Polysaccharides quantified in sediment cores from coastal vegetated ecosystems - Inga Hellige; Aman Akeerath Mundanatt; Theresa-Marie Fett; Mirco Wölfelschneider; Jennifer Prugger; Jana K Geuer; Svenja Reents (PANGAEA, 2025)
50-cm deep sediment cores were taken in saltmarsh, seagrass, mangroves and unvegetated areas around the German Bight, Malaysia and Columbia in 2022 and 2023. Up to 3 points per ecosystem were sampled along a transect, in total 93 cores were analysed. Carbohydrates were sequentially extracted using MilliQ-water and 0.3 M EDTA for later analyses. Polysaccharides were screened using microarray analysis following the method described by Vidal-Melgosa et al. (2022). Briefly, sediment extracts from MilliQ-water and EDTA were combined in equal volumes, and 30 μL of the mixture was transferred into wells of 384-microwell plates. Two consecutive two-fold dilutions were performed using a printing buffer (55.2% glycerol, 44% water, 0.8% Triton X-100). The plates were then centrifuged at 3,500 exttimes g for 10 minutes at 15 °C. Each microarray was individually probed with a monoclonal antibody (mAb), and binding was detected using a secondary antibody conjugated to alkaline phosphatase. In the presence of its substrate, this reaction produced a colorimetric signal. Developed arrays were scanned at 2400 dots per inch, and binding signal intensity was quantified using Array-Pro Analyzer 6.3 software (Media Cybernetics).